PROSES PRODUKSI KATALIS ZEOLIT X DAN UJI AKTIFITAS DALAM PROSES PENUKARAN ION KALSIUM - Widayat Widayat; A. Sadikky DP; H. Anggraeni (Diponegoro University, 2012)
Zeolie is a material that used in chemical process industry. Zeolite commonly used as catalyst, adsorbent adnion exchanger.Zeolite can be obtained from natural resources and synthetic in industry. The type of zeolitethatused as ion exchanger zeolite X. Zeolite X can produced hy uding hydrogel process and clay process. Thisreasearch was study influencing of temperature and ratio sodium hydroxide (NaOH) to water glass in zeolite Xpreparation. Crystallity of zeolite X was analyzed with X-ray diffraction (XRD) and the activity was used asion exchanger. Response variabel in this research is weight of zeolite X and the capability as ion exchanger.Ion exchange test that used for exchange of calsium. Calsium ion was analizyed by using complexometrymethod. The results of this research shown that zeolit X was obtained in temperature 100oC and rationweight of sodium hidroxide (NaOH) to water glass 1:2. The zeolite X can be used as ion exchanger especiallyfor calsium ion.